Rancang Bangun Sistem Monitoring pada Tanaman Greenhouse Berbasis Internet of Things (IOT) - Regita, Nazifah Dilla; Nasution, Mulkan Iskandar; Nasution, Nazaruddin (IAI Nasional Laa Roiba Bogor, 2024)
A greenhouse is a structure where plants are grown using agricultural techniques in an environment where the climate can be managed. The aim of research on a prototype smart greenhouse monitoring system based on the internet of things (IoT) is to create a tool that makes it easier for farmers to monitor plants without having to physically visit the greenhouse. Power supply, ESP32, soil pH sensor, capacitive soil moisture sensor, DHT22 sensor, HC-SR04 ultrasonic sensor, relay, LCD, and water pump are some of the electronic components used in this smart greenhouse system. By using sensor data and microcontroller commands to read soil pH, soil moisture, water availability, temperature and air humidity, the Smart Greenhouse Monitoring System was successfully operated. For example, the soil humidity sensor measures soil humidity if <40% the water pump will turn on. The room temperature and humidity sensor measures if the temperature is >33 °C and the room humidity is <40% then the water pump will turn on. The Ultrasonic Sensor detects the level of water availability with a limit of <10cm and will provide a notification as a warning that the water supply will run out. To manage the smart greenhouse output devices and display data on the LCD and Blynk, logic operators are used to process all data received from the devices.